2010
DOI: 10.1159/000319322
|View full text |Cite
|
Sign up to set email alerts
|

Are Overweight and Obese Youth at Increased Risk for Physical Activity Injuries?

Abstract: Objective: To determine whether relationships between physical activity and physical activity injuries are modified by BMI status in youth. Method: Data were obtained from the 2006 Canadian Health Behaviour in School-Aged Children survey; a representative study of 7,714 grade 6–10 youth. A sub-sample of 1,814 were re-administered the survey in 2007. Analyses considered relationships among the major variables in theory-driven crosssectional and longitudinal analyses. Result: Among normal weight youth, cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
16
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 32 publications
3
16
1
4
Order By: Relevance
“…3,7 For example, studies have reported that youths with the highest level of sport participation were more than 2–4 times more likely to be injured than those with the lowest level of sporting activity. 8,9 However, the evidence pertaining to the relationship between body composition and sport injury in adolescents has been inconclusive. For example, one recent study used a cross-sectional survey to investigate the role of BMI, as a proxy for body composition, in sport injury in high-school-age youths.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,7 For example, studies have reported that youths with the highest level of sport participation were more than 2–4 times more likely to be injured than those with the lowest level of sporting activity. 8,9 However, the evidence pertaining to the relationship between body composition and sport injury in adolescents has been inconclusive. For example, one recent study used a cross-sectional survey to investigate the role of BMI, as a proxy for body composition, in sport injury in high-school-age youths.…”
mentioning
confidence: 99%
“…Conversely, another study found that the volume of sport participation, but not BMI, was related to increased injuries in overweight and obese youths. 8 Thus, the association between overweight or obesity and sport injury is clearly an area of research that demands further clarity.…”
mentioning
confidence: 99%
“…Increased mass results in a greater load on the joints, particularly in the lower limbs, increasing the potential for lower-extremity sprains/strains, and fractures. 75,78 Additionally, when an individual with a higher BMI classification is exposed to a form of contact such as a hit during a sporting activity, the forces generated would be greater because of the increased body mass, resulting in increased torque on the bones, thus intensifying the amount of damage to the joints. 75 The evidence that does not support an association between BMI and injury may be explained by the concept that some overweight and obese individuals may choose to limit their participation in certain physical activities due to the limitations caused by their increase in body weight and size.…”
Section: Body Compositionmentioning
confidence: 99%
“…75,78 Additionally, when an individual with a higher BMI classification is exposed to a form of contact such as a hit during a sporting activity, the forces generated would be greater because of the increased body mass, resulting in increased torque on the bones, thus intensifying the amount of damage to the joints. 75 The evidence that does not support an association between BMI and injury may be explained by the concept that some overweight and obese individuals may choose to limit their participation in certain physical activities due to the limitations caused by their increase in body weight and size. 79 They may also be less likely to return to exercise post-injury, which may affect recovery time and therefore their return to normal daily activity.…”
Section: Body Compositionmentioning
confidence: 99%
“…The major limitation of these studies was that physical activity participation was not co-assessed, which in itself is a major predictor of injuries. Warsh et al (Canada) [1] performed multivariateanalysestoovercomethislimitation;theydetermined factors associated with physical activity injuries in a representative survey of 9,672 Canadian school children (grades6-10).Theresultswereconfirmedinasubsamplefolloweduplongitudinally.Asexpected,youthwhoengagedin high levels of physical activity experienced higher risks for physical activity injuries. However, a modifying effect of weight status on this relationship was not discernible.…”
mentioning
confidence: 99%